2000
DOI: 10.1054/bjoc.2000.1458
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis of breast cancer cell lines

Abstract: The extensive chromosome rearrangements of breast carcinomas must contribute to tumour development, but have been largely intractable to classical cytogenetic banding. We report here the analysis by 24-colour karyotyping and comparative genomic hybridization (CGH) of 19 breast carcinoma cell lines and one normal breast epithelial cell line, which provide model examples of karyotype patterns and translocations present in breast carcinomas. The CGH was compared with CGH of 106 primary breast cancers. The lines v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 29 publications
11
72
1
Order By: Relevance
“…We did not detect any homozygous deletions either in the breast tumors or in the breast cancer cell lines tested. In addition, all the breast cancer cell lines used in the present study have previously been shown by cytogenetic analysis to contain at least one normal chromosome 16 (Davidson et al, 2000). Even though we obtained an indication for an intragenic LOH in one of the cell lines analysed, this alteration is not expected to be su cient to explain the altered WWOX gene expression observed.…”
Section: Discussioncontrasting
confidence: 52%
“…We did not detect any homozygous deletions either in the breast tumors or in the breast cancer cell lines tested. In addition, all the breast cancer cell lines used in the present study have previously been shown by cytogenetic analysis to contain at least one normal chromosome 16 (Davidson et al, 2000). Even though we obtained an indication for an intragenic LOH in one of the cell lines analysed, this alteration is not expected to be su cient to explain the altered WWOX gene expression observed.…”
Section: Discussioncontrasting
confidence: 52%
“…Rearrangements of 8p were identified in a set of breast, colon and pancreatic cancer cell lines, for most of which we had previously obtained SKY (spectral karyotyping) karyotypes (Davidson et al, 2000;Abdel-Rahman et al, 2001;Sirivatanauksorn et al, 2001; available at http:// www.path.cam.ac.uk/Bpawefish).…”
Section: Resultsmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) also shows frequent losses of distal 8p in breast, colorectal, prostate, bladder and other cancers (e.g. Davidson et al, 2000;AbdelRahman et al, 2001;Karan et al, 2003;Hurst et al, 2004;Hwang et al, 2004), and more recently array CGH has begun to provide more detail of these losses (e.g. Paris et al, 2003;Douglas et al, 2004;Hurst et al, 2004;Nakao et al, 2004;Garcia et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome 8 aberrations are very frequent in breast tumours, resulting in losses of 8p and gains of 8q (Mertens et al, 1995;Adeyinka et al, 2000;Davidson et al, 2000;Forozan et al, 2000;Kytölä et al, 2000;Höglund et al, 2001;Rummukainen et al, 2001;Struski et al, 2002;Teixeira et al, 2002;Ferti et al, 2004; Online CGH Tumour Database; http://cgap.nci.nih.gov/Chromosomes/ RecurrentAberrations). The 8p11 -p21 region contains several potential TSG and oncogenes (Adélaïde et al, 1998(Adélaïde et al, , 2003Ugolini et al, 1999;Conte et al, 2002;Ray et al, 2004).…”
Section: Comparison Of Our Results With Literature Datamentioning
confidence: 99%